Efektivitas Permainan Tradisional Dakon untuk Meningkatkan Kemampuan Berhitung pada Anak Tunagrahita - Lika Hestyaningsih; Wiwien Dinar Pratisti (JIP (Jurnal Intervensi Psikologi), 2021)
The ability to count is one of the useful abilities for intellectual disability children in everyday life. Fun and easy numeracy skills methods can be a means to improve numeracy skills in intellectual disability children. The dakon game applied in this study can be a means to improve numeracy skills in intellectual disability children because in the dakon game, children are trained to count using kecik dakon seeds in solving arithmetic problems. This study aims to test the effectiveness of traditional dakon games to improve the numeracy skills of intellectual disability children. This research is an experimental study that uses a one group pretest-posttest design. In this study involved three students with intellectual disability children. The results of the analysis with the Shapiro Wilk statistical test showed that the traditional dakon game was effective to improve numeracy skills in intellectual disability children.